Mitochondrial bioenergetics, metabolism, and beyond in pancreatic β-cells and diabetes - Rivera Nieves, Alejandra María; Wauford, Brian Michael; Fu, Accalia (Frontiers in Molecular Biosciences, 2024)
In Type 1 and Type 2 diabetes, pancreatic β-cell survival and function are impaired. Diabetes involves additional etiologies including dysfunction in insulin-sensing hepatic, muscle, and adipose tissues as well as immune cells. An important determinant of metabolic health across these various tissues is mitochondria function and structure. This review focuses on the role of mitochondria in diabetes pathogenesis, with a specific emphasis on pancreatic β-cells. These dynamic organelles are obligate for β-cell survival, function, replication, insulin production, and control over insulin release. Therefore, it is not surprising that mitochondria are severely defective in diabetic contexts. Mitochondrial dysfunction poses challenges to assess in cause-effect studies, prompting us to assemble and deliberate the evidence for mitochondria dysfunction as a cause or consequence of diabetes. Understanding the precise molecular mechanisms underlying mitochondrial dysfunction in diabetes and identifying therapeutic strategies to restore mitochondrial homeostasis and enhance β-cell function are active and expanding areas of research. In summary, this review examines the multidimensional role of mitochondria in diabetes, focusing on pancreatic β-cells and highlighting the significance of mitochondrial metabolism, bioenergetics, calcium, dynamics, and mitophagy in the pathophysiology of diabetes. We describe the effects of diabetes-related gluco/lipotoxic, oxidative and inflammation stress on β-cell mitochondria, as well as the role played by mitochondria on the pathologic outcomes of these stress paradigms. By examining these aspects, we provide updated insights and highlights areas where further research is required for a deeper molecular understanding of the role of mitochondria in β-cells and diabetes.